THE EFFECT OF EDUCATION AND TRAINING ON PERFORMANCE THROUGH EMPLOYEE JOB PLACEMENT ASSESSMENT - Kusnawan, Adi; Dalle, Juhriyansyah; Ahmad, Karyono Ibnu (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
Education, training, and assessment of placement are essential for companies, therefore, this research aims to analyze the effect of training on job placement assessment. This emphasized the effect of education; and job placement assessment on employee performance; and also, education on employee performance through job placement assessment. Furthermore, the study was performed on 87 employees of PT. Gunung Limo and PT. Putra Sarana Transborneo, which became the sample size chosen randomly. The data obtained were grouped with the use of a questionnaire and subsequently evaluated using the path analysis. Besides, the result showed some effects of (1) education and (2) training on job placement assessment; (3) education, (4) training and (5) job placement assessment on performance; and also the effect of (6) education and (7) training on the employee?s performance through job placement assessment by a company?s education management unit.